2021
DOI: 10.1002/slct.202101790
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Coupling‐Cyclocondensation Reaction Sequence to Access a Library of Ring‐C Bridged Pyrimidino‐tetrahydrothebaines and Pyrimidinotetrahydrooripavines

Abstract: Ring‐C bridged 1‐(pyrimidinyl)tetrahydrothebaines were convenience synthesized by a consecutive three‐component alkynylation–cyclocondensation sequence starting from 1‐ethynyl‐7α,8α‐(2,5‐dioxo‐N‐phenylpyrrolidino)‐[3,4‐h]‐6,14‐endo‐etheno‐tetrahydrothebaine, aroyl chlorides, and amidinium hydrochlorides. Several derivatizations and transformations of selected 1‐pyrimidinyl substituted tetrahydrothebaines were carried out. The analgesic activity of new type of hybrid compounds in the tail‐flick test in rats was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The 18R-hydroxy (185, 46%) and 19S-hydroxy (186, 43%) isomers were separated by preparative TLC, and the structure of the 18R-hydroxy compound (185) was verified by X-ray analysis. Selective protection of the least hindered 7α-hydroxymethyl group of the 19-OH compound (186) via benzylation provided the 7α-benzyloxymethyl derivative (188).…”
Section: Isomerizationmentioning
confidence: 99%
See 3 more Smart Citations
“…The 18R-hydroxy (185, 46%) and 19S-hydroxy (186, 43%) isomers were separated by preparative TLC, and the structure of the 18R-hydroxy compound (185) was verified by X-ray analysis. Selective protection of the least hindered 7α-hydroxymethyl group of the 19-OH compound (186) via benzylation provided the 7α-benzyloxymethyl derivative (188).…”
Section: Isomerizationmentioning
confidence: 99%
“…For the successful 6-O-demethylations, an OR (R = H, alkoxy) or an NH 2 group was required in the 20 position. Shults et al [187,188] investigated the O-demethylation reactions of thebaine-succinimide adducts with boron tribromide, in which demethylation of alkyl methyl ether (6-O-demethylation) and/or demethylation of aryl methyl ether (3-O-demethylation) was observed, depending on the character of the substrate. Coop et al [159] reported on the unusual 6-O-demethylation of 20-methylthevinol through hydroboration (BH 3 /H 2 O 2 ), whereas Husbands et al studied the reactions of buprenorphine (96) with N-halosuccinimide derivatives in an acidic milieu [189].…”
Section: -O-demethylationmentioning
confidence: 99%
See 2 more Smart Citations